Accounting for leases : impacts and effects of choice of method on the financial ratios of companies listed on the stock exchange of Singapore - Tan, Eng Teck (2014)
Historically, rentals on leases could be charged to profit and loss account without further disclosure about the future obligations under the lease agreement. However, with the implementation of Statement of Accounting Standard (SAS) 15 which was effective from 1st January 1985, the prevailing practice was changed.